Mitochondrial D-loop sequence variation among Italian horse breeds - Cozzi, Maria Cristina (BioMed Central, 2004)
The genetic variability of the mitochondrial D-loop DNA sequence in seven horse breeds bred in Italy (Giara, Haflinger, Italian trotter, Lipizzan, Maremmano, Thoroughbred and Sarcidano) was analysed. Five unrelated horses were chosen in each breed and twenty-two haplotypes were identified. The sequences obtained were aligned and compared with a reference sequence and with 27 mtDNA D-loop sequences selected in the GenBank database, representing Spanish, Portuguese, North African, wild horses and an Equus asinus sequence as the outgroup. Kimura two-parameter distances were calculated and a cluster analysis using the Neighbour-joining method was performed to obtain phylogenetic trees among breeds bred in Italy and among Italian and foreign breeds. The cluster analysis indicates that all the breeds but Giara are divided in the two trees, and no clear relationships were revealed between Italian populations and the other breeds. These results could be interpreted as showing the mixed origin of breeds bred in Italy and probably indicate the presence of many ancient maternal lineages with high diversity in mtDNA sequences.